A new skilled emigration dynamic: Portuguese nurses and recruitment in the southern European periphery - Pereira, C. (New and old routes of Portuguese emigration: Uncertain futures at the periphery of Europe, 2019)
Philippine and Indian nurses have been emigrating for many years, but Portu-guese nurses and other South and East Europeans have recently started to replace them in the UK. This study focuses on the recent migration of Portuguese nurses – both as emigrants and immigrants – within the European area. The research mixes extensive and intensive methodologies. Health agencies start-ed to recruit heavily among Portuguese nurses after 2008, which often led to their decision to leave the country with a guaranteed job abroad. In turn, this dynamic of emigration being motived by institutional and recruitment networks was caused by a structural factor: the barriers erected in 2010 by UK immigration pol-icies against the contracting of nurses from outside the EU, which led the job agencies to search for nurses inside Europe. The chapter’s main finding is that alt-hough the push factor of economic recession and increased unemployment that hit the European periphery after the 2008 financial crisis played a role in the out-flow of Portuguese nurses, it was the pull factor that was more significant. The second finding is that this new mass emigration of nurses is not just a Portuguese phenomenon but rather is in keeping with other Southern and East European pe-ripheral countries.